Zero‑Shot Slice Policy Transfer for Cloud‑RAN Resource Allocation under Fronthaul and SLA Constraints. - M. Alkafrawi, Ismail; M. M. Mohamede, Ibrahim; Ali Abouda, Abdulla (Scientific Journal of University of Benghazi, 2025)
ABSTRACT Cloud RAN requires fast, SLA aware resource allocation across heterogeneous slices (eMBB, URLLC, mMTC). Training a dedicated controller for every slice is impractical; policies must generalize to unseen slice semantics spanning latency, reliability, rate, burstiness, and mobility. A coupled radio–compute–fronthaul allocation problem is formulated, and Zero Shot Slice Policy Transfer (ZSPT) is introduced as a semantics to policy mapping that operates without per slice training by distilling a high quality convex surrogate into a lightweight scheduler. In this paper zero shot performance was evaluated against Proportional Fair (PF) and the convex surrogate, reporting throughput, Jain’s fairness, UE rate percentiles, and SLA violation probability with bootstrap 95% confidence intervals. In a representative scenario, ZSPT matched PF on unseen slices, while the convex surrogate increased fairness and substantially raises 5th percentile UE rates.